2023
DOI: 10.18016/ksutarimdoga.vi.1102770
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organic Matter and Different Nitrogen Sources in Annual Ryegrass Cultivation on Forage Yield and Quality

Abstract: Üretimde verim ve kaliteyi artırmak için gübre uygulaması vazgeçilmezdir. Yoğun tarımsal faliyetler sonucunda her geçen gün verim düşmekte ve çevre kirliliği artmaktadır. Bu çalışmanın amacı; farklı organik madde ve azot kaynaklarının tek yıllık çimin verim ve kalitesi üzerine etkilerinin belirlenmesidir. Çalışma 2018-2020 yıllarında tesadüf blokları deneme desenine göre üç tekrarlı olarak yürütülmüştür. Tek yıllık çim hiçbir uygulama yapılmadan (kontrol), çiftlik gübresi (3 ton da-1), tavuk gübresi (300 kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…Consequently, there are so many interactions related to years and fertilizers. Similar results were also reported by various researchers [22,32,40]. When the interactions related to dry matter yield were evaluated overall, it was clear that the combined usage of the fertilizers was more effective than their single application.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Consequently, there are so many interactions related to years and fertilizers. Similar results were also reported by various researchers [22,32,40]. When the interactions related to dry matter yield were evaluated overall, it was clear that the combined usage of the fertilizers was more effective than their single application.…”
Section: Discussionsupporting
confidence: 89%
“…However, NDF and ADF ratios varied in manure, humic acid, and nitrogen fertilizer, and their combinations. Similar to our research results, Demiray and Parlak [32] reported that fertilizer applications affected NDF and ADF ratios at different rates, and this situation was closely related to climatic factors in the study in which he investigated the effects of organic matter and different nitrogen sources applied to annual ryegrass.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations